(untitled) (Applied Biological Research, 2018)
The present study was aimed to assess urban-rural disparity in the physical activity pattern of government school children of Punjab (India). A survey was conducted on 1050 children (11-17 years) randomly selected from urban and rural government schools to collect information on their physical activity pattern (school sports, leisure time physical activity/LTPA and mode of commuting to school) and sedentary behaviour (screen time). The study revealed no urban-rural disparity in mean time spent by school children in LTPA (5.1 h wk-1each) and screen activities (9.8 for urban vs. 9.5 h wk-1for rural subjects). Urban school children were spending (p≤ 0.05) more time (7.5 h wk-1) in school sports, than rural school children (6.6 h wk-1). The percentage of active commuters was more from rural schools (92%) as compared to urban schools (85%). Overall the children were spending on an average 6.9, 5.1 and 9.6 h wk-1in school sports, LTPA and screen activities, respectively. Based on AAP and WHO levels, children from government schools of Punjab did not possess sedentary behaviour as they had adequate physical activity level, low screen time and weremostly active commuters.